The chemokine landscape: one system multiple shades - Cecchinato, Valentina; Martini, Veronica; Pirani, Edisa; Ghovehoud, Elaheh; Uguccioni, Mariagrazia (Frontiers in Immunology, 2023)
Leukocyte trafficking is mainly governed by chemokines, chemotactic cytokines, which can be concomitantly produced in tissues during homeostatic conditions or inflammation. After the discovery and characterization of the individual chemokines, we and others have shown that they present additional properties. The first discoveries demonstrated that some chemokines act as natural antagonists on chemokine receptors, and prevent infiltration of leukocyte subsets in tissues. Later on it was shown that they can exert a repulsive effect on selective cell types, or synergize with other chemokines and inflammatory mediators to enhance chemokine receptors activities. The relevance of the fine-tuning modulation has been demonstrated in vivo in a multitude of processes, spanning from chronic inflammation to tissue regeneration, while its role in the tumor microenvironment needs further investigation. Moreover, naturally occurring autoantibodies targeting chemokines were found in tumors and autoimmune diseases. More recently in SARS-CoV-2 infection, the presence of several autoantibodies neutralizing chemokine activities distinguished disease severity, and they were shown to be beneficial, protecting from long-term sequelae. Here, we review the additional properties of chemokines that influence cell recruitment and activities. We believe these features need to be taken into account when designing novel therapeutic strategies targeting immunological disorders.